(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
A novel tungsten carbide (WC)-reinforced nickel (Ni)-based laser cladding layer prepared by in-situ synthesized process. The growth mechanism of the cladding layer was explored. Furthermore, the mechanism of the influence of different concentrations for CeO2/Y2O3 doping on the microstructures, wear and corrosion resistance of in-situ synthesized WC-reinforced Ni-based cladding layer were analyzed. The results revealed that the optimal content of rare earth oxides using the CeO2 content of 0.75% and the Y2O3 content of 1.50%, which exhibit outstanding hardness (660HV0.2) and excellent wear resistance. In addition, the minimum corrosion rate of the coating were 0.002770 mm/a and 0.0022548 mm/a, with the noble Ecorr (-0.12549 V/-0.49924 V) and lower Icorr (2.3550×10-7 A·cm2/1.9170×10-7 A·cm2). The doping of rare earth oxides in the cladding layer excellently enhances the wear and corrosion resistance, which was mainly ascribed to the rare earth oxides have better refining grain and purifying effect on the cladding layer organization.